Incidence and Survival of Gynecologic Sarcomas in England. Issue 5 (1st June 2015) - Francis, Matthew; Dennis, Nicola L.; Hirschowitz, Lynn; Grimer, Robert; Poole, Jason; Lawrence, Gill; Nordin, Andy
Abstract : Objective: Gynecologic sarcomas account for approximately 3% to 4% of all gynecologic malignancies and are associated with poor outcomes compared with gynecologic carcinomas. The aim of this study is to report the incidence and survival rates of the main gynecologic sarcomas using national English cancer registration data. Methods/Materials: Records of gynecologic sarcomas diagnosed between 1985 and 2008 were extracted from the English National Cancer Data Repository. ICD-O3 morphology codes were used to assign tumor records to specific histologic subgroups. Incidence and 5-year relative survival rates were calculated. Results: There were 5316 new cases of gynecologic sarcoma diagnosed in England between 1985 and 2008. Incidence rates increased significantly in the early 1990s, probably due to coding changes. Age-specific incidence rates were highest in women aged between 45 and 64 years. In the most recent period studied (2001–2008), incidence rates fluctuated between 8 and 9.6 per million. The most common anatomical site was the uterus (83% of all diagnoses), and the most common histologic diagnosis was leiomyosarcoma (52% of all diagnoses). Overall 5-year relative survival increased significantly between 1985–1989 and 2000–2004, from 34% to 48%. Conclusions: Gynecologic sarcoma incidence rates have varied little since 1993, whereas survival has improved significantly. These results are consistent with previously published small series and case studies, and provide a more complete picture of gynecologic sarcoma incidence and survival patterns in England.